Novel synthetic routes to prepare biologically active quinoxalines and their derivatives: a synthetic review for the last two decades - Abdul Malek, Emilia; Khatoon, Helena (MDPI, 2021)
Quinoxalines, a class of N-heterocyclic compounds, are important biological agents, and a significant amount of research activity has been directed towards this class. They have several prominent pharmacological effects like antifungal, antibacterial, antiviral, and antimicrobial. Quinoxaline derivatives have diverse therapeutic uses and have become the crucial component in drugs used to treat cancerous cells, AIDS, plant viruses, schizophrenia, certifying them a great future in medicinal chemistry. Due to the current pandemic situation caused by SARS-COVID 19, it has become essential to synthesize drugs to combat deadly pathogens (bacteria, fungi, viruses) for now and near future. Since quinoxalines is an essential moiety to treat infectious diseases, numerous synthetic routes have been developed by researchers, with a prime focus on green chemistry and cost-effective methods. This review paper highlights the various synthetic routes to prepare quinoxaline and its derivatives, covering the literature for the last two decades. A total of 31 schemes have been explained using the green chemistry approach, cost-effective methods, and quinoxaline derivatives’ therapeutic uses.